IMPLIKASI BIJAK BERMEDIA SOSIAL DALAM MENCEGAH PENGGUNAAN NAPZA DI KALANGAN REMAJA - As’ari, Hasim; Adly, Suci Aristi; Rahmadhani, Dira; Chaira, Kuntum; Pakpahan, Ade Putra; Ramadhani, Zakia; Prameswari, Ulan; Situmeang, Von Braun; Shelawati, Ernita; Syahreza, Lucky (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
The existence of technology that makes it easier for us to communicate by providing social media continues to grow. Although initially the use of social media was to make it easier for us to receive and share information with each other. However, apart from that, we often also encounter negative impacts resulting from social media. This happens due to lack of wisdom and lack of understanding in the use of social media, which leads to abuse. In fact, this abuse also creates a desire to try deviant things, such as drug use. For this reason, socialization activities regarding drugs are carried out as well as wise use of social media so that there is deeper understanding and growing awareness and strengthening self-control, both in terms of managing social media and saying no to drugs. In order to achieve the objectives of the activity, an interactive lecture method was used. The result of this activity is to raise awareness among teenagers so that they do not easily fall into negative things through their social media.